Epithermal neutron beam for BNCT at the JSI TRIGA reactor - modelling and experimental verification - Maučec, Marko (Radiology and oncology (Ljubljana), 1999)
It has been reported that satisfactory thermal/epithermal neutron beams for Boron lVeutron Ćapturc, Therapy (BNCT) could be designed at TRIGA research reactors, which are generally perceived as being safe to install and operate in populated areas. This contribution presents the most recent research activities in this field at the Jožef Stefan Institute TRIGA reactor, where anepithermal neutron beam for BNCT is being developed. Experimental verification of Monte Carlo simulation results proves the quality and wide applicability of the developed 3-D model, particularly of the reactor core andirradiation channels. Due to high attenuation of the epithermal neutron flux (fi epi = 4.1x106 n/cmZs, two orders of magnitude belozu the therapeutic limit) the irradiation facility in the current stage of development is not appropriate for the clinical BNCT treatments. Furthermore, the contribution ofthe 2.5 mm airgap surrounding the facility is unacceptably high, thus makingthe relative gamma dose (Dy/fiepi) almost 60-times higher than therapeutically rcc- ommended. Nevertheless, using gamma shielding of Pb or Biand LiF or Li2C03 (thermal neutron cut-off, the quality of the epithermal neutron beam would be significantly upgraded and hecome appropriate fnr iii vitro studies of boron compound transport in malignant tumour cells or smallerlahoratory animals.
Keywords: Boron neutron capture therapy; Monte carlo method; Neoplasms; Nuclear reactors; nuklearna medicina; onkologija; radiologija; Radiotherapy; rak (medicina); zdravljenje